Constitutive oxidants from hepatocytes of male iPLA2β-null mice increases the externalization of phosphatidylethanolamine on plasma membrane - Wong, Heng Yeng; Langlotz, Monika; Gan-Schreier, Hongying; Xu, Weihong; Staffer, Simone; Tuma-Kellner, Sabine; Liebisch, Gerhard; Merle, Uta; Chamulitrat, Walee (Free radical research, 2021)
We have found that group VIA calcium-independent phospholipase A2 (iPLA2β) has specificity for hydrolysis of phosphatidylethanolamine (PE) in mouse livers. Phospholipids (PLs) are transported to plasma membrane and some PLs including PE are externalized to maintain membrane PL asymmetry. Here we demonstrated that hepatocytes of iPLA2β-null (KO) mice showed an increase in PE containing palmitate and oleate. We aimed to examine whether externalization of PE on the outer leaflets could be affected by iPLA2β deficiency and its modulation by reactive oxygen species (ROS) or apoptosis. As duramycin has high affinity to PE, we used duramycin conjugated with biotin (DLB) and streptavidin 488 as a probe for detection of externalized PE. Compared to WT, naïve KO hepatocytes showed an increase in both PE externalization and ROS generation. These events were observed in male but not in female KO mice. Hydrogen peroxide or menadione treatment enhanced PE externalization to the same extent for both male/female WT and KO hepatocytes. By indirect immunofluorescence, DLB-streptavidin staining was observed as small punctuated spots on the cell surface of menadione-treated KO hepatocytes. Unlike the reported PS externalization, CD95/FasL treatment did not lead to any increase in PE externalization, and iPLA2β deficiency-dependent PE externalization was also not correlated with apoptosis. Thus, constitutive (but not induced) ROS generation in iPLA2β-deficient hepatocytes leads to PE externalization observed only in male mice. Such PE externalization may imply detrimental effects regarding further oxidation of PE fatty acids and the binding with pathogens on the outer leaflets of hepatocyte plasma membrane.
Gesehen am 04.12.2021